PREVENSI BUDGETARY SLACK SEBAGAI DAMPAK TEORI AGENSI DENGAN METODE REFRAMING KOMUNIKASI NEURO LINGUISTIK PROGRAM (NLP) - Bestari, Ruli (Jurnal Akuntansi AKUNESA, 2014)
Budgeting is the most important thing to do in Corporation as a design guideline work in the future. Participative Budgeting is one of the budget common method which is almost done over the world. Participative budgeting can be authority delegation from superiors to subordinates, of course subordinates can participate in their corporate budgeting. However, participative budgeting often misused by subordinates just as good performance assessment from superiors that tend to make budgetary slack behavior. Budgetary slack happen caused by different of interest between superiors and subordinates,common called agency theory.Deviant behavior like Budgetary slack can be recovered with sisthematic pattern communication of both. Reframing of Neuro Linguistic Program can be good solution to change from deviant behavior be better behavior with rearrange sentence in communication to their self or others. Reframing helps communication disturbances from superiors to subordinates which is not good to be more attractive and motivative, so that it can make better atmosphere seems like trust,closer and solid teamwork of both which can prevent Budgetary Slack behavior.Key Feature : Budgetary slack, Neuro Linguistic Program, Budgeting,Reframing